Prevalence of anhedonia, anxiety, and their impact on food consumption among postgraduate Qassim University students - Alrehaili, Sarah; Afifi, Abeer A.; Algheshairy, Reham M.; Bushnaq, Taqwa; Alharbi, Talal Ali F.; Alharbi, Hend F. (Frontiers in Nutrition, 2024)
Objectives: A prevalent symptom of many mental health issues, such as depression, is anhedonia, which is the inability to feel joy or pleasure. Tension-induced sensations, anxious thoughts, and bodily alterations are the hallmarks of anxiety. One known environmental factor that affects mental health is diet. In this implication, eating appetising meals has been proposed to reduce unpleasant feelings like worry. This study aimed to indicate whether eating habits among postgraduate students are related to symptoms of anhedonia and/or anxiety.In a cross-sectional study, responses were collected from a total of 393 postgraduate students. Each student self-answered the General Anxiety Disorder-7, Snaith-Hamilton Pleasure Scale for anhedonia, and the Food Consumption Questionnaire and reported the body weight.The prevalence of anhedonia was 28%, moderate anxiety and severe anxiety were 15.7% and 10.9%, respectively. In this research, results showed that sugary foods, fast food, and fried foods were positively associated with anxiety and anhedonia. However, fruits and vegetables were negatively associated with anxiety and anhedonia. Linear regression showed that fruit and drinking water consumption was significant with the number of meals/day. There was no significance between the number of meals per day and anhedonia; however, there was statistical significance with the total GAD-7 scale score regarding the number of meals/per day.